Sistem Pengendali Perangkat Elektronik melalui Voice Assistant dengan Metode Rapid Application Development (RAD) - Rina Nurain Mokodompit; Quido C Kainde; Ferdinan I. Sangkop (Program Studi Teknik Informatika, 2023)
The purpose of this research was to assist each householder controling electronic devices when traveling in a quite distance. Therefore, apply microcontroller technology in the form of an electronic device control system via voice commands was necessity in other that it can cover a wide distance when it was connected to the internet. In this research, Voice command was controlled through a voice assistant on the user's cellphone. The way to implement it was by using several microcontroller components, including the NodeMCU ESP8266 and ESP32-CAM modules which function as indoor surveillance camera. whereas other supporting components, used FTDI as a USB to connect the ESP32-CAM as the power source, relays as automatic switches that could supply or cut off current electric to the electronic devices, and jumper cables as a link to components. Then, the system was tested both software and hardware used to find out whether the system was running well as expected. The workflow of the electronic device control system through this voice assistant began with the user giving voice commands through the voice assistant to control electronic devices both to turn on and off devices and to open CCTV cameras. The results of research showed that the voice assistant can properly accepted the voice commands given with a time span of 1 second for each command to turn on or turn off electronic devices. Likewise with the camera from the ESP32-CAM which functioned properly so that the browser can displayed indoor live stream video. That's why, the electronic device control system via voice assistant had been successfully designed and running properly using all the components mentioned above. So that users can controled electronic devices even though they were far from home by utilizing the existing internet connection now.